Philosophy of Education and Pedagogy: Peculiarities of Interaction - Vakhovskyi, Leonid (Journal of Education Culture and Society, 2023)
Aim. The aim of the article is to determine the status and purpose of philosophy of education, and to identify the peculiarities of its relationship with educational practice and pedagogical science.Concept. Philosophy of education and pedagogy explore different aspects of the same subject field – education. Realising different research functions, they do not act as competitors, but, on the contrary, have the potential for mutual complementarity and reciprocal strengthening of their cognitive capabilities.Results. Philosophy of education as a branch of applied philosophy is not an instrumental tool and cannot directly influence educational practice. It is designed to provide comprehension and understanding of the most important problems of the theory and practice of education. The role of mediator is played by another science of education – pedagogy.Conclusion. The most productive form of relationship between philosophy of education and pedagogical science is their interaction, which contributes to the mutual enrichment, building up and the fullest realisation of their special research capabilities. Pedagogy has a choice of philosophical and educational concepts to develop educational theories which are verified by experiment and directly implemented in practice. Philosophy of education realises its theoretical functions at all stages of educational activity.Cognitive value. The article presents a new perspective on the problem of the relationship between educational philosophy and educational practice. It is argued that the most efficient channel of transferring philosophical and educational ideas into practice is pedagogical science.Keywords: philosophy of education, educational practice, pedagogy, comprehension, understanding, interaction, functions of philosophy of education